Factors Affecting The Use and Development of Solar Energy in Iran's Agricultural Sector - Mohammadi, Mohsen; Yavari, Gholamreza (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
The paper seeks to identify factors led some farmers to use renewable energy in their poultry farms. The research was a practical study in terms of goal and a descriptive-correlation study in terms of methodology. The population of the study was composed of Semnan Province poultry farmers that used any type of renewable energy in their farms. Based on the farmer's viewpoints, the most important factors made farmers use renewable energy in their poultries were poultry farm revenue, bank loans with low interest rate, and technology and equipment availability. Also, according to stepwise regression, 78.4% of the variance of the dependent variable was accounted for by the variables of economic, technical, subsidies reform, and policies factors. Therefore, financial incentives such as bank loans with low interest, distribution of technical equipment requirements and supportive legislation can be effective on the development of renewable energy use among other farmers.Article History: Received Nov 16th 2016; Received in revised form January 12nd 2017; Accepted 3rd February 2017; Available onlineHow to Cite This Article: Mohammadi, M and Yavari, G. (2017) Factors affecting the use and development of solar energy in Iran's agricultural sector. International Journal of Renewable Energy Development, 6(1),45-53.http://dx.doi.org/10.14710/ijred.6.1.45-53